2009
DOI: 10.2174/138527209789578081
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxy-6-methyluracil, an Efficient Scavenger of Peroxyl Radical in Water

Abstract: The reactivity of 5-hydroxy-6-methyluracil (HMU) towards peroxyl radicals generated from the aerobic thermal decomposition of 2,2 -azo-bis(2-amidinopropane)dihydrochloride (AAPH) has been investigated. The oxidation product of HMU is dihydro-5,5,6-trihydroxy-6-methylpyrimidin-2,4-dion-e (94%). The relative oxidation rate of HMU vs. quercetin by peroxyl radicals generated from AAPH has been measured as 0.20 ± 0.04 at 54.6°C, hence HMU is the effective scavenger of peroxyl radicals. The overall kinetic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Indeed its rate constant for reaction with ethylbenzene peroxyl radicals was reported as k = 2.6 × 10 4 M −1 s −1 . A recent investigation has shown that during the thermal decomposition of 2,2′-azo-isobutyronitrile (AIBN) in 2-propanol at 75 °C (in air) HMU prevented the radical-mediated oxidation of the solvent (to form acetone) as efficiently as the well-known antioxidant quercetin, by reacting with initiator-derived peroxyl radicals to yield product 4 . However, the mechanism for such peroxyl-radical-quenching is far from being understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed its rate constant for reaction with ethylbenzene peroxyl radicals was reported as k = 2.6 × 10 4 M −1 s −1 . A recent investigation has shown that during the thermal decomposition of 2,2′-azo-isobutyronitrile (AIBN) in 2-propanol at 75 °C (in air) HMU prevented the radical-mediated oxidation of the solvent (to form acetone) as efficiently as the well-known antioxidant quercetin, by reacting with initiator-derived peroxyl radicals to yield product 4 . However, the mechanism for such peroxyl-radical-quenching is far from being understood.…”
mentioning
confidence: 99%
“…However, the mechanism for such peroxyl-radical-quenching is far from being understood. It was suggested to occur by radical addition to the ring in the 6-position followed by disproportionation, by analogy with the known reactivity of uracil derivatives with hydroxyl radicals (Scheme ) …”
mentioning
confidence: 99%